The Christmas crush : a novel - Douglas, Noelle (Alcove Press, 2024)
"Marketing executive Elena Voss's newest assignment for Sparkle Cookie, a large cookie conglomerate, was meant to be a much-needed break from her toxic boss and the stressful city. She never expected to get into a public--and embarrassing--argument with a sexy baker in New Hope, Pennsylvania. But the townsfolk aren't exactly thrilled about a corporate chain bakery coming in to ruin their small-town feel. Lawrence Higgins-and his dog Sugar-have been a beloved staple in New Hope for years. Their bakery specializes in cookies, but with Sparkle Cookie's upcoming grand opening, he's worried about rent spikes and stolen customers. Elena wants to write Lawrence off as an opponent she can crush, but his good looks and passion for baking make it difficult to stay professional. Elena and Lawrence immediately butt heads at a town hall meeting. When a cookie competition makes them join forces, sparks fly, and they find first impressions are often wrong. Can their blossoming connection survive the ensuing cookie war?"--